PENGATURAN PAJAK RESTORAN ATAS FOOD TRUCK MENURUT UNDANG-UNDANG NOMOR 28 TAHUN 2009 TENTANG PAJAK DAERAH DAN RETRIBUSI DAERAH - Ahmad Munir; Dea Arifka Andini (universitas islam darul ulum lamongan, 2017)
The development of restaurant business requires entrepreneurs to make creative innovation in business such as the existence of Foof Truck. Food Truck is a new model of bussiness for selling food by a car so that it can mobile to another places. The definition of restaurant in the restaurant tax regulation does not mention Food Truck, but there are similar concepts so that there are multi interpretations in that sense. Not only interpret the notion of the restaurant, but also understanding the subject, mandatory, and object of restaurant taxes. This study aims to analysis the Food Truck model whether it is included or not in the restaurant tax category in restaurant tax arrangements. The method used in this research is normative legal method, so the study in this research is focused with the approach of legislation and conceptual approach. The results of analysis of the Local Taxation and Retribution regulations will indicate whether Food Truck is or is not included in the restaurant taxes category.